Histopathological characteristics and treatment options of papillary thyroid carcinoma less than 1 cm at Hue University of Medicine and Pharmacy Hospital - Dang, Cong Thuan; Ngo, Quy Tran; Tran, Thi Nam Phuong; Tran, Van Bao; Le, Thanh Huy; Le, Vi (Tạp chí Y Dược Huế, 2025)
Background: Thyroid cancer is the most common type of endocrine malignancy. More than 90% of cases are diagnosed as differentiated thyroid carcinoma, with the papillary type being the most prevalent. Papillary thyroid carcinoma (PTC) with a maximum diameter ≤1 cm is associated with a distinct prognosis and treatment approach compared to larger PTCs. Objectives: To investigate Histopathological Characteristics and Treatment Approaches for Thyroid Carcinomas ≤1 cm at the Hospital of Hue University of Medicine and Pharmacy. Materials and Methods: A cross-sectional and retrospective descriptive study on 122 patients definitively diagnosed with thyroid carcinoma, with the size of the tumor ≤1 cm, at the University of Medicine and Pharmacy Hospital, Hue University, between February 2024 and December 2024. Results: 72.1% of patients were under 55 years of age, with the female-to-male ratio of 7:1. PTC accounted for 95.9%, with 66.5% being the classic subtype; 74.6% had solitary tumors; 15.6% with thyroid capsule invasion; 77.9% without lymph node involvement; 99.2% without vascular invasion; 95.1% were diagnosed at stage I. Total thyroidectomy was performed in 66.4% of cases, accompanied by 59% lymph node dissection, while 33.6% underwent lobectomy. 74.6% and 67.2% of cases were indicated for I-131 and Thyrosine, respectively. 12.3% had postoperative complications, and hypocalcemia was the most common complication (10.7%). Conclusion: Papillary thyroid carcinoma accounted for most cases (95.9%). Surgery is the primary treatment option (100%). The postoperative complication rate was relatively low (12.3%), with a statistically significant association between the type of surgical procedure and risk of postoperative hypocalcemia observed.